Las TIC y nuevas narrativas. - Narváez Nolivos, Carlos Andrés (2016)
Reflection about several of the most significant changes and modifications in terms of products of cultural industries and communication processes that are influenced by the TIC. The text includes several approaches in terms of the impact unleashed by the digital age around contemporary narratives that society confronts; the sense of public and private in the midst of new social networks current consumption-musical production and how digitalization introduces new languages that give new meaning to the contemporaneity. One of the major impacts in contemporary society demands knowledge of the emerging digital symbolic systems. The accelerated technological revolution of the 21st century has meant to bring advantages and opportunities accelerating communication production, distribution and consumption of content, thus transforming the social organization and its current economic system consolidating a perspective and contemporary vision of humanity and it is surroundings reason which is deserves a constant and dynamic reflection. The daily impact of ICT and the internet have given rise to a new symbolic environment capable of producing and creates a communicative settings through ways to digital represent reality, social relationship, art and knowledge. Understand and interpret the consequences of them ICT in the communication faces to new forms of narrating and built sense of contemporaneity forms clearly affecting life every day, labour relationship, the economy and the same identity.